Pengaruh Kompetensi Profesional Guru Terhadap Aktivitas Belajar Siswa, Kemudahan Memahami Materi Pembelajaran dan Hasil Belajar Siswa Pada Mata Pelajaran IPA di SMP Rayon II Kabupaten Sigi - Gafil Gafil; Samsurizal M. Suleman; Sarjan N. Husain (Mitra Sains, 2019)
The objective of this research was to know the influence and the relationship among teachers’ professional competence to students learning activity, the ease of understanding learning material and students learning outcomes on IPA subject at SMP Rayon II Sigi Regency. This research was a formal research which found out the relationship among the influence of students learning activities Y1, the ease of understanding learning materials Y2 and student learning outcomes Y3 in IPA subject. To measure the teachers professional competence (X) is obtained by using the observation sheet that contained the teachers assessment activities, variable Y1 obtained by observations on the implementation process of learning in the classroom, variable Y2 about the ease of understanding the learning materials obtained by questionnaire and variable Y3 on student learning outcomes obtained of the results of tests conducted by each teacher that being a sample in this study. The results indicated that the teachers’ professional competence had very real influence on students' learning activities and ease of understanding learning material but not real on student learning outcomes. In conclusion, teachers’ professional competence is a matter that needs to be developed by teachers with special autonomy so that they had more professional responsibility. Achievement of the average value of the percentage of the activity of 27 teachers with students as much as in 1080 reached 76.85% or in the good criteria according to the size specified by Depdiknas (2004).